Toxicology and carcinogenesis studies of black cohosh root extract (CASRN 84776-26-1) administered by gavage to Sprague Dawley (Hsd:Sprague Dawley SD) rats and female B6C3F1/N mice - National Toxicology Program (National Toxicology Program technical report series, 2023)
This is a work of the US government and distributed under the terms of the Public Domain.